Development of a biofilm inhibitor molecule against multidrug resistant Staphylococcus aureus associated with gestational urinary tract infections - P, Balamurugan; M, Hema; Kaur, Gurmeet; V, Sridharan; P.C, Prabu; M.N, Sumana; Princy, S. Adline (Frontiers in Microbiology, 2015)
Urinary Tract Infection (UTI) is a globally widespread human infection caused by an infestation of uropathogens. Eventhough, Escherichia coli is often quoted as being the chief among them, Staphylococcus aureus involvement in UTI especially in gestational UTI is often understated. Staphylococcal accessory regulator A (SarA) is a quorum regulator of S. aureus that controls the expression of various virulence and biofilm phenotypes. Since SarA had been a focussed target for antibiofilm agent development, the study aims to develop a potential drug molecule targeting the SarA of S. aureus to combat biofilm associated infections in which it is involved. In our previous studies, we have reported the antibiofilm activity of SarA based biofilm inhibitor, (SarABI) with a 50% minimum biofilm inhibitory concentration (MBIC50) value of 200 µg/mL against S. aureus associated with vascular graft infections and also the antibiofilm activity of the root ethanolic extracts of Melia dubia against uropathogenic E. coli. In the present study, in silico design of a hybrid molecule composed of a molecule screened from M. dubia root ethanolic extracts and a modified SarA based inhibitor (SarABIM) was undertaken. SarABIM is a modified form of SarABI where the fluorine groups are absent in SarABIM. Chemical synthesis of the hybrid molecule, 4-(Benzylamino)cyclohexyl 2-hydroxycinnamate (henceforth referred to as UTI Quorum-Quencher, UTIQQ ) was then performed, followed by in vitro and in vivo validation. The MBIC¬50 and MBIC90 of UTIQQ were found to be 15 µg/mL and 65 µg/mL respectively. Confocal laser scanning microscopy (CLSM) images witnessed biofilm reduction and bacterial killing in either UTIQQ or in combined use of antibiotic gentamicin and UTIQQ. Similar results were observed with in vivo studies of experimental UTI in rat model. So, we propose that the drug UTIQQ would be a promising candidate when used alone or, in combination with an antibiotic for staphylococcal associated UTI.